Measurements necessary for assessing the net ecosystem carbon budget of croplands - Smith, Pete; Lanigan, Gary; Kutsch, Werner L.; Buchmann, Nina; Eugster, Werner; Aubinet, Marc; Ceschia, Eric; Béziat, Pierre; Yeluripati, Jagadeesh B.; Osborne, Bruce; Moors, Eddy J.; Brut, Aurore; et al. (Agriculture, ecosystems & environment, 2010)
There are a number of methods that can be used to help assess carbon budgets at the site to continental scales. Eddy covariance (EC) networks have been developed over the last decade and have been used to make many advances in our understanding. However, eddy covariance measurements of CO 2 and water vapour exchanges quantify the fluxes only on short time scales, but do not assess the impacts of long-term processes that contribute to biogeochemical cycling in croplands, such as harvest or residue removal and other management practices, so many other supplementary measurements are required to attribute different components of the carbon flux. Such methods include isotope studies, chamber flux measurements of C and other greenhouse gases, inventories of above- and below-ground biomass as well as management in- and outputs, book-keeping modelling, process modelling, experimental manipulation and earth observation (e.g. remote sensing). In this review, we summarise the component fluxes that make up the total cropland carbon budget, describe the key fluxes and methods used to estimate them, and examine how they need to be integrated to obtain the net ecosystem carbon budget of European croplands. We describe the uncertainties and difficulties inherent at each stage and how these can be minimised.